Systemic inflammation is higher in peripheral artery disease than in stable coronary artery disease. Issue 2 (April 2015) - Rein, Philipp; Saely, Christoph H.; Silbernagel, Günther; Vonbank, Alexander; Mathies, Rainer; Drexel, Heinz; Baumgartner, Iris
Abstract: Objective: The knowledge on the level of systemic inflammation in peripheral artery disease (PAD) is less well established than that in coronary artery disease (CAD). Systemic inflammation frequently coincides with atherosclerosis, but also with various traits of the metabolic syndrome (MetS). The individual contribution of CAD, PAD, and the MetS to inflammation is not known. Methods: We enrolled a total of 1396 patients, 460 patients with PAD Fontaine stages IIa-IV verified by duplex ultrasound (PAD group) and 936 patients free of limb claudication undergoing coronary angiography, of whom 507 had significant CAD with coronary stenoses ≥50% (CAD group), and 429 did not have significant CAD at angiography (control group). Results: C-reactive protein (CRP) was significantly higher in the PAD than in the CAD or in the control group (0.86 ± 1.85 mg/dl versus 0.44 ± 0.87 mg/dl and 0.39 ± 0.52 mg/dl, respectively, p < 0.001 for both comparisons). These significant differences were confirmed when patients with and subjects without the MetS were analyzed separately. In particular, within the PAD group, CRP was significantly higher in patients with the MetS than in subjects without the MetS (1.04 ± 2.01 vs. 0.67 ± 1.64 mg/dl; p = 0.001) and both, the presence of PAD and the MetS proved to be independently associated with CRP in analysis of covariance (F = 31.84; p < 0.001 and F = 10.52; p = 0.001, respectively). Conclusion: Inflammatory activity in PAD patients is higher than in CAD patients and is particularly high in PAD patients affected by the MetS. Low grade systemic inflammation is independently associated with both the MetS and PAD. Highlights: C-reactive protein is higher in PAD patients than in CAD patients. White blood count is higher in PAD patients than in CAD patients. This holds true in patients with and without the Metabolic Syndrome. Within PAD patients, CRP and WBC are associated with the metabolic trait of low HDL-C.